A Novel Automatic Approach for Calculation of the Specific Binding Ratio in [I-123]FP-CIT SPECT - Mahmudur G. M. Rahman; Muhammad M. Islam; Tetsuya Tsujikawa; Hidehiko Okazawa (Diagnostics, 2020)
A fully automatic method for specific binding ratio (SBR) calculation in [123I]ioflupane single-photon emission computed tomography (SPECT) studies was proposed by creating volumes of interest of the striatum (VOIst) and reference region (VOIref) without manual handling to avoid operator-induced variability. The study involved 105 patients (72 ± 10 years) suspected of parkinsonian syndrome (PS) who underwent [123I]ioflupane SPECT. The 200 images from our previous study were used for evaluation and validation of the new program. All patients were classified into PS and non-PS groups according to the results of clinical follow-up. A trapezoidal volume of interest (VOIt) containing all striatal intensive counts was created automatically, followed by VOIst setting using the previous method. SBR values were calculated from the mean values of VOIst and VOIref determined by the whole brain outside of VOIt. The low count voxels in the VOIref were excluded using an appropriate threshold. The SBR values from the new method were compared with the previous semi-automatic method and the Tossici–Bolt (TB) method. The SBRs from the semi- and fully automatic methods showed a good linear correlation (r > 0.98). The areas under the curves (AUCs) of receiver operating characteristic analysis showed no significant difference between the two methods for both our previous (AUC > 0.99) and new (AUC > 0.95) data. The diagnostic accuracy of the two methods showed similar results (>92%), and both were better than the TB method. The proposed method successfully created the automatic VOIs and calculated SBR rapidly (9 ± 1 s/patient), avoiding operator-induced variability and providing objective SBR results.